Development Of Teaching Materials For Writing Recount Text For Class VIII Students - Sugianto, Sugianto; Rachmawati, Rachmawati; Budiyono, Herman (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2019)
This study was aimed to produce the steps of developing and learning material of writing recount text effectively and effisiently in writing of recount text learning at MTs Asyafi’iyah. The developing model is adopted from Borg and Gall Model. In this case the writer use 6 main steps of Borg and Gall because according the writer analysis 6 main steps is effectively and effisiently in making the product of learning material. The sixth main steps is: 1) Research & Information Collecting, 2) Planning, 3) Develop Preliminary Form of Product, 4) Field Testing and Product Revision, 5) Final Product Revision, 6) Disseminassion and Implementation. Offeral findings showed that developing learning material o f writing recount text for students of the Yunior High School/Religion Yunior High School at eight grade is good qualify. Expert evaluate that this multimedia and learning material is good to be media and help the teacher to deliver the material and it could be motivated the students in learning process. Generally, based on the data analysis, expert validation or field trial showed that the quality of English Learning process in recount text writing for the eight grade of Yunior High School or Religion Yunior High School is good, so this developing product could be used as media in English learning process.